Comparison of pre operative fine needle aspiration cytology diagnosis and histopathological diagnosis of salivary gland tumours - S. Rajasekhar Reddy; P. Swarna Latha; B. Chaitanya (International Journal of Medical Research and Review, 2015)
Objective: FNAC is a useful method for evaluating suspicious salivary gland lesions due to its low cost, minimum morbidity, rapid turnaround time, high specificity, and sensitivity. The present study was undertaken to diagnose salivary gland tumors based on the cytomorphology and to correlate with histopathology wherever available and to review the histologic and cytomorphological features in discordant cases and evaluate the possible reasons of misinterpretation.Methods: The study was both prospective and retrospective. All the cases of salivary gland tumors that had fine needle aspiration cytology reports were taken from records of Nizam’s Institute of Medical Sciences. This study was done between January 2000 to May 2008.Results: A total of 135 cases of salivary gland neoplasms were identified during 8 1/2 period of our study. 1. Histologic correlation was available for 36 cases 2. There is a concordance between cytology and histopathology in 31/36 cases (86.1%). In three cases (8.3%) diagnostic possibilities were given. 94.1% of pleomorphic adenoma cases had concordance (16/17). 3. The number of discordant cases were 5/36 (13.9%) and the discordance was due to scant cellularity and rarity of the lesions. Majority of the cases 4(80%) it was underdiagnosis and in one case (20%) it was over diagnosis.Conclusion: FNAC is a highly reliable technique for pre-operative diagnosis of salivary gland tumors in the hands of experienced pathologists. However, there still remain few cases that may be inaccurately diagnosed on cytology due to overlapping features and in these cases histopathology is the only modality for final diagnosis.